Engineering challenges of intrafirm technology reuse. Issue 3 (19th December 2018) - Corin Stig, Daniel; Bergsjö, Dag
Abstract: Companies derive additional value from technological investments by repeatedly applying them across different product lines in their portfolios. Technology reuse strategies have helped to increase efficiency in leveraging research and development investments, but the attempts to explain how to duplicate such results for technology reuse at the engineering level are missing. While there are synergetic effects to the reuse of technologies, there are also transaction costs that limit the benefits in practice. This paper presents a model, along with three examples, of technology reuse to help account for these transaction costs and mitigate the fallacy of perceiving technologies as reusable "off‐the‐shelf" elements.